Stroke Risk Assessment and Emergency Mobile Application in a Hospital in Thailand - Siwipa Pruitikanee; Jinda Kongcharoen; Supattra Puttinaovarat; Thotsaphon Yaifai; Sasikorn Chaitada (Tehran University of Medical Sciences, 2022)
Background: Cerebrovascular diseases or stroke tend to cause high mortality in Thailand. An essential responsibility of a hospital is the development of medical care to support the safety of patients. For this purpose, a smartphone application was developed for the risk assessment and emergency system for stroke treatment in a hospital in Thailand.  Methods: The proposed application involved the risk assessment related to the occurrence of stroke evaluated by the health status and face image using analytical geometry and face detection technology. The social network Application Programming Interface (API), LINE Notify API, and Global Positioning System (GPS) were used to inform the Stroke team in the Suratthani hospital about emergency cases, followed their requirement in 2020. Results: From the testing, the facial angulation classification, calculated using a support vector machine (SVM), had 92.38% accuracy. The system also provided an emergency call and text messaging that includes patient's current location and personal information to the stroke team directly, which gave an opportunity for the patient to receive treatment quickly. Conclusion: The emergency system can help quickly perform the risk assessment of stroke. Our proposed system provides automated management.